2017
DOI: 10.3389/fpls.2017.00214
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis NAC Transcription Factor JUNGBRUNNEN1 Exerts Conserved Control Over Gibberellin and Brassinosteroid Metabolism and Signaling Genes in Tomato

Abstract: The Arabidopsis thaliana NAC transcription factor JUNGBRUNNEN1 (AtJUB1) regulates growth by directly repressing GA3ox1 and DWF4, two key genes involved in gibberellin (GA) and brassinosteroid (BR) biosynthesis, respectively, leading to GA and BR deficiency phenotypes. AtJUB1 also reduces the expression of PIF4, a bHLH transcription factor that positively controls cell elongation, while it stimulates the expression of DELLA genes, which are important repressors of growth. Here, we extend our previous findings b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 81 publications
(123 reference statements)
0
23
0
Order By: Relevance
“…Furthermore, Al can trigger signal transduction pathways upon which phytohormones act [37]. In tomato, the overexpression of the Arabidopsis NAC transcription factor JUNGBRUNNEN1 (AtJUB1) exerts conserved control over gibberellin and brassinosteroid metabolism and signaling genes controlling growth [71]. Importantly, NAC genes may be regulated by ABA-dependent or ABA-independent pathways because of the difference in their promoter elements [72].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Al can trigger signal transduction pathways upon which phytohormones act [37]. In tomato, the overexpression of the Arabidopsis NAC transcription factor JUNGBRUNNEN1 (AtJUB1) exerts conserved control over gibberellin and brassinosteroid metabolism and signaling genes controlling growth [71]. Importantly, NAC genes may be regulated by ABA-dependent or ABA-independent pathways because of the difference in their promoter elements [72].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, proline, a likely important osmoprotectant in plants (Ashrafa and Fooladb, ), accumulated in MusaNAC042 overexpressors compared to control plants, concomitant with an improved tolerance to drought and high salinity stress (Tak et al ., ). Of note, elevated levels of proline, in addition to the osmoprotectant trehalose, were also detected in tissues of Arabidopsis and tomato AtJUB1 overexpressors (Shahnejat‐Bushehri et al ., ; Wu et al ., ), suggesting that compatible solute osmolytes contribute to the enhanced drought tolerance in these plants in accordance with the important role of osmotic adjustment during drought conditions (Blum, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the function of the NAC transcription factor JUNGBRUNNEN1 (JUB1) for the response of tomato to drought stress. Previously, we showed that JUB1 (ANAC042) from Arabidopsis thaliana (hereafter, AtJUB1) functions as a central regulator of plant longevity and the interplay between growth and stress responses (Shahnejat-Bushehri et al, 2016;Wu et al, 2012). We reported that AtJUB1 exerts its role in controlling the response to stress in part through dampening cellular hydrogen peroxide (H 2 O 2 ) level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NAC factor JUNGBRUNNEN1 (JUB1) negatively regulates senescence, while it positively affects tolerance to various abiotic stresses (Wu et al ., ; Ebrahimian‐Motlagh et al ., ). Metabolite profiling revealed elevated levels of proline and trehalose in JUB1 overexpressors (Wu et al ., ; Shahnejat‐Bushehri et al ., ). However, it is currently unknown whether genes affecting the metabolite levels are directly controlled by JUB1.…”
Section: Introductionmentioning
confidence: 97%